Natural orifice transluminal endoscopic surgery and localized resection for colorectal neoplasia - Cahill, Ronan A (Baishideng Publishing Group Co., Limited, 2010)
Modern methods of surgical intervention have the potential to provide effective, definitive management of early stage colorectal neoplasia by truly minimally invasive means. Margin-free clearance of early colonic neoplasia from within the intestinal lumen can already now be effected by endoscopic submucosal dissection in the colon and transluminal endoscopic microsurgery (TEM) in the rectum. Natural orifice transluminal endoscopic surgery (NOTES) offers the potential for providing transmural, full thickness excision as TEM does but at sites in the colon proximal to the rectum. The next conceptual advance required to make this practice an effective reality lies in evolving surgical regional staging strategies to effectively partner localized resective approaches and allow their deployment as definitive curative therapy. As the most compelling modality for nodal status ascertainment in the absence of lymphatic basin excision for other malignant disease processes, it seems timely to reconsider sentinel node biopsy in cancer of the colon and rectum. Whether by this means or indeed any other, such an ability to confidently identify patients with node negative disease would allow nascent innovative techniques flourish as definitive management for confined (N0) T1 and T2 cancers and so allow the application of available advanced technology for clinical benefit. Conversely, the development of a specific clinical niche for NOTES (whether, as here, for full thickness localized colonic excision or nodal staging alone) would greatly benefit the evolution and incorporation of this surgical strategy into clinical care paradigms.